CÓMO VEN SU FUNCIÓN LOS AUDITORES DE PROCESO AUTOMÁTICO DE DATOS (PAD) - Rivera León, Félix A. (2007)
The way in which the PAD auditors see their function is very important for the success of any auditing internal, external or from third people. Unfortunately, the PDA administrador (Data Process) often considers the auditor like the man who shoots the wounded after the battle, while the PAD auditor perceive his function like preventive maintenance in the analysis and evaluation of reliability and integrity of data process systems. This article discusses the way in which the PAD auditor and the PD administration sees the function of the auditing and suggests how they can work together to improve that function.